Toll-like receptors in ocular immunity and the immunopathogenesis of inflammatory eye disease. Issue 1 (16th December 2005) - Chang, J H; McCluskey, P J; Wakefield, D
Abstract : Microbial agents have an important role in the pathogenesis of various inflammatory eye diseases, such as uveitis and keratitis. Microbial infections of the eye such as microbial keratitis, ocular onchocerciasis, bacterial endophthalmitis, viral retinitis, and other infectious uveitis are unfortunately common. In addition, microbial agents have been implicated in the pathogenesis of "non-infectious" immune mediated diseases such as HLA-B27 associated acute anterior uveitis. Toll-like receptors (TLR) are a family of pattern recognition receptors that initiates rapid host innate immune response to microbial components known as pathogen associated molecular patterns, which are unique to a given class of microbes, such as lipopolysaccharide of Gram negative bacteria. Recent in vitro and in vivo studies have demonstrated the expression and function of TLRs in the eye, with significant implications for better understanding of ocular immunity and the pathogenesis of inflammatory eye diseases affecting the cornea, uvea, and retina.